AB0138 Immunomodulatory Profile of Tofacitinib in the Treatment of Chronic Arthritis in Rabbits. (9th June 2015) - Perez-Baos, S.; Barrasa, J.I.; Gratal, P.; Larranaga-Vera, A.; Lopez-Oliva, F.; Aguilera, L.; Largo, R.; Herrero-Beaumont, G.
Abstract : Background: Tofacitinib (TOFA) is a Janus Kinase (JAK) inhibitor approved for the treatment of rheumatoid arthritis (RA) in different countries. TOFA treatment has recently been shown to selectively inhibit the expression of several chemokines from synovial biopsies from RA patients that were treated over 28 days (1). However, TOFA did not modify the expression of various pro-inflammatory cytokines, nor histopathological synovial inflammation, including macrophage infiltration. In this regard, animal models may allow a better understanding of the consequences of JAK inhibition in chronic arthritis (CA). Our group developed a model of CA in rabbits that mimics severe human RA, thereby allowing investigation of TOFA and its consequences in synovial tissue. Objectives: We have analyzed the early treatment effect of TOFA in a model of CA, aiming to evaluate early tissue changes rather than the final therapeutic effect. Methods: A well-established model of antigen-induced CA was induced in 20 rabbits via four, weekly intra-articular injections of ovalbumin in previously immunized rabbits (CA group). After two intra-articular injections, 10 CA rabbits were treated with TOFA (10mg/kg/day, orally) for two weeks (CA+TOFA) and 10 healthy rabbits were used as controls. Animals were euthanised four weeks after intra-articular challenge, when we collected serum and synovial samples for different studies. Results: CA animals showed reduced weight gain compared to controls, which was partially prevented by TOFA (weight gain, kg; Control: 0.8±0.05; CA: -0.09±0.06*; CA+TOFA: 0.18±0.1*#; *p<0.05 vs Control; #p<0.05 vs CA). CA animals showed a substantial increase in serum C-reactive protein (CRP), not improved by TOFA. Synovial membranes of CA animals showed marked intimal hyperplasia, activation of synovial stroma, and intense inflammatory infiltration. TOFA treatment partially reverted synovitis (Krenn Score; Control: 0.9±0.3; CA: 7.6±0.2*; CA+TOFA: 6.6±0.2*#; *p<0.05 vs control; #p<0.05 vs CA). Synovial density of macrophages was also elevated in CA animals, and was not modified by TOFA treatment. Regarding gene expression, TOFA treatment effectively inhibited the synovial expression of matrix metalloproteinase 1 (MMP-1) (96% inhibition, p=0.002) and MMP-3 (100% inhibition p=0.007), compared to CA animals. TOFA also decreased the expression of the chemokine CCL2 (MCP-1) (95% inhibition, p=0.001), and the pro-inflammatory cytokines interleukin (IL)-6 (51% inhibition, p=0.037), and tumor necrosis factor (TNF) (90% inhibition, p=0.022), compared to CA animals. TOFA treatment did not modify the expression of IL-1β, inducible nitric oxide synthase (iNOS) or cyclooxygenase (COX)-2. Conclusions: In synovial tissue with intense inflammatory activity, TOFA treatment mainly inhibited the expression of MMPs and, to a lesser extent, the expression of other pro-inflammatory mediators. These data suggest that this drug could act as an immunomodulator of the chronic inflammatory response. TOFA does not induce a fast or drastic reduction in cellular recruitment within synovial tissue, but a moderate and generalized decrease of cytokines with a stronger effect on MMPs. References: Boyle DL et al. The JAK inhibitor tofacitinib suppresses synovial JAK1-STAT signalling in rheumatoid arthritis. Ann Rheum Dis. 2014 [epub ahead of print] Disclosure of Interest: None declared